(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2019)
This paper deals with design and simulation of Proportional plus Derivative (PD) controller for two links robotic arm. The PD controller was used to compute the required joint’s torque for tracking the desired trajectory. The Particle Swarm Optimization (PSO) algorithm has been used in order to tune the gains of the proportional and derivative parts of PD controller. Simulation results show an efficient and robust behavior of the proposed controller. Two cases of simulation tests were carried out. The first was tracking a sine wave trajectory while the second was tracking the same trajectory with the presence of disturbance torque on the dynamic model of the robotic arm. The simulation results were compared with the presence of disturbance torque on the dynamic model of the robotic arm. The simulation results were compared with the results obtained by other researchers, for similar robotic arm properties and same trajectory. The proposed controller offers a simple method for trajectory tracking problem with a satisfactory efficiency. A Mean Square Error (MSE) criterion was used to study the efficiency of the proposed controller in tracking the desired trajectory.